Noninvasive Self-Powered Iontophoresis Mask Based on a Water-Driven Fiber Battery - Yiwen Wang; Yalin Tang; Ming Li; Tong Xu; Xuyan Lu; Deteng Zhang; Ning Yu; Mingwei Tian (Research)
Facial masks are often used to treat skin problems, and the introduction of microcurrent ion penetration technology can improve drug penetration and help facial tissue repair. However, most microcurrent stimulation masks contain a direct current power supply and require external power sources, resulting in inconvenient portability and use. Herein, we provide a noninvasive self-powered iontophoresis mask with a water-driven power supply, which is continuously prepared by self-constructing equipment to continually construct a zinc–manganese fiber battery (Zn-Mn@FB) and then seamlessly integrated with a nonwoven cellulose-based superabsorbent fiber substrate. The mask can be activated by water and is simple and portable to use. Zn-Mn@FB demonstrated a capacitance retention of 65.22% (1,000 cycles) and a specific discharge capacity of 27.33 mAh/g (10 cm), which improved with an increase in battery length to up to 41 mAh/g (30 cm). The iontophoresis mask exhibited a stable current within the safe range of 0.09 to 0.59 mA (within 800 s) after water activation, and the drug penetration area increased by 102.64%. The platform is expected to become a practical device for enhanced transdermal drug delivery in the medical field, with the potential to integrate additional components for expanded functionality and productization in the future.